TRANSFORMASI KARAKTERISTIK KOMUNIKASI DI ERA KONVERGENSI MEDIA - Gushevinalti Gushevinalti; Panji Suminar; Heri Sunaryanto (Universitas Bunda Mulia, 2020)
ABSTRACT The development of communication technology has caused a shift or change in the concept of communication in particular the characteristics of mass communication. This study aims to find changes about the characteristics of mass communication in the current era of media convergence. In addition, to describe new forms of media that can be categorized into mass communication. The research method uses a qualitative approach to data collection techniques through document studies and literature review and interviews in mass communication courses. The informants of this study were lecturers of mass communication courses at the Bachelor of Communication Studies and Journalism FISIP S1 University of Bengkulu, as well as two groups of students who explained the characteristics of mass communication. The results showed that the development of communication technology at this time had contributed thoughts in the discussion about the transformation of the characteristics of mass media communication from conventional to digital. New forms of media that can be categorized based on these characteristics are online media, such as print media that have been changed by online systems, digital television and radio streaming. The characteristics of the mass media in some literatures have changed in one direction or have been interactive. Keywords; transformation, mass communication, convergence, new media, characteristics ABSTRAK Perkembangan teknologi komunikasi telah menyebabkan pergeseran atau perubahan dalam konsep komunikasi khususnya karakteristik komunikasi massa. Penelitian ini bertujuan untuk menemukan perubahan tentang karakteristik komunikasi massa di era konvergensi media sekarang ini. Selain itu, untuk mendeskripsikan bentuk media baru yang dapat dikategori kedalam komunikasi massa. Metode penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui studi dokumen dan kajian literatur dan wawancara pada matakuliah komunikasi massa. Informan penelitian ini adalah dosen pengasuh matakuliah komunikasi massa di prodi S1 Ilmu Komunikasi dan S1 Jurnalistik FISIP Universitas Bengkulu, serta dua kelompok mahasiswa yang memaparkan tentang karakteristik komunikasi massa. Hasil penelitian menunjukkan bahwa perkembangan teknologi komunikasi saat ini telah memberikan kontribusi pemikiran pada pembahasan mengenai transformasi karakteristik komunikasi media massa dari yang konvensional menuju digital. Bentuk media baru yang dapat dikategorikan berdasarkan karakteristik tersebut yaitu media online, seperti media cetak yang dirubah dengan sistem online, televisi digital dan radio streaming. Karakteristik media massa dalam beberapa literature menjadi berubah kakteristiknya tidak satu arah lagi atau sudah interaktif. Kata kunci; transformasi, komunikasi massa, konvergensi, media baru, karakteristik